Double Orifice Fissured Subaortic Membrane in the Adult - Zampi, Giordano; Cottini, Marzia; Pergolini, Amedeo; Polizzi, Vincenzo; Musumeci, Francesco (International Journal of Cardiovascular Practice, 2017)
Left ventricle outflow tract obstruction is a relatively common form of congenital heart disease, occurring in 2.8 out of 10,000 live births and accounts for 3-6% of congenital heart diseases. Subvalvular aortic stenosis can be either a fixed stenosis resulting from subaortic membrane or a dynamic stenosis because of hypertrophic cardiomyopathy. We described an original and rare image of double orifice fissured subaortic membrane in the adult.